From materials to structures : advancement through innovation : proceedings of the 22nd Australasian Conference on the Mechanics of Structures and Materials, ACMSM 22, Sydney, Australia, 11-14 December 2012 /: advancement through innovation : proceedings of the 22nd Australasian Conference on the Mechanics of Structures and Materials, ACMSM 22, Sydney, Australia, 11-14 December 2012. (©2013) - Unknown
No abstract available